The effect of 6 weeks dynamic neuromuscular stabilization (DNS) breathing exercises on postpartum balance and quality of life in primiparous women with low back pain - Vajihe Ghavipanje; Naser Mohammad Rahimi; Farideh Akhlaghi (Mashhad University of Medical Sciences, 2022)
Introduction: Postpartum period is a critical stage, the consequences of which can lead to problems such as decreased balance and quality of life. The present study was performed aimed to investigate the effect of dynamic neuromuscular stabilization (DNS) breathing exercises on postpartum balance and quality of life in primiparous women with low back pain. Methods: This randomized controlled clinical trial was conducted in 2020 on 24 primiparous women with postpartum low back pain referred to Ommol-banin Obstetrics and Gynecology Hospital in Mashhad. The subjects were randomly divided into two experimental (n=12) and control (n=12) groups. The variables of static and dynamic balance and quality of life before and after the study were measured by the Sharpened-Romberg test, time up and go test, and quality of life questionnaire, respectively. The experimental group participated in the training program for six weeks. Data were analyzed by SPSS software (version 23), parametric test, and Repeated Measures Analysis of Variance (RM-ANOVA). P< 0.05 was considered statistically significant. Results: In the experimental group, changes in static balance with open and closed eyes, dynamic balance and quality of life after delivery were significant (P<0.005). But no significant difference was observed in the control group and in the variables of static balance with open eyes (P=0.701), with closed eyes (P=0.220), dynamic balance (P=0.339) and quality of life (P=0.210). A significant difference was observed between the two groups in the research variables in the study of intergroup results of the repeated measures test (P<0.005). Conclusion: DNS exercises are suitable, low-cost and low risk intervention, which can be used as one of the best interventions for postpartum women.